As we grow old: nutritional considerations for older patients on dialysis - Johansson, Lina; Fouque, Denis; Bellizzi, Vincenzo; Chauveau, Philippe; Kolko, Anne; Molina, Pablo; Sezer, Siren; Ter Wee, Pieter M; Teta, Daniel; Carrero, Juan J (Nephrology, dialysis, transplantation, 2017)
The number of older people on dialysis is increasing, along with a need to develop specialized health care to manage their needs. Aging-related changes occur in physiological, psychosocial and medical aspects, all of which present nutritional risk factors ranging from a decline in metabolic rate to assistance with feeding-related activities. In dialysis, these are compounded by the metabolic derangements of chronic kidney disease (CKD) and of dialysis treatment per se, leading to possible aggravation of protein-energy wasting syndrome. This review discusses the nutritional derangements of the older patient on dialysis, debates the need for specific renal nutrition guidelines and summarizes potential interventions to meet their nutritional needs. Interdisciplinary collaborations between renal and geriatric clinicians should be encouraged to ensure better quality of life and outcomes for this growing segment of the dialysis population.